2015
DOI: 10.3122/jabfm.2015.03.140082
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Electronic Health Record (EHR) Reminder on Human Papillomavirus (HPV) Vaccine Initiation and Timely Completion

Abstract: Background Initiation and timely completion of the HPV vaccine in young women is critical. We compared initiation and completion of HPV vaccine among women in two community-based networks with electronic health records: one with a prompt and reminder system (prompted cohort) and one without (unprompted cohort). Methods Female patients aged 9–26 years seen between March 1, 2007 and January 25, 2010 were used as retrospective cohorts. Patient demographics and vaccination dates were extracted from the electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 25 publications
(30 reference statements)
2
52
0
Order By: Relevance
“…The authors suggested that this combined strategy may have supported the creation of a common agenda that facilitates HPV vaccine series initiation. (48) A recent literature review of interventions to increase HPV vaccination rates suggested that there was sufficient evidence to support the use of Community Preventive Task Force recommendations related to client reminder and recall systems as well as provider assessment and feedback. (49) Thus, future interventions may benefit from considering point-of-care reminders that simultaneously prompt physicians and patients to discuss HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that this combined strategy may have supported the creation of a common agenda that facilitates HPV vaccine series initiation. (48) A recent literature review of interventions to increase HPV vaccination rates suggested that there was sufficient evidence to support the use of Community Preventive Task Force recommendations related to client reminder and recall systems as well as provider assessment and feedback. (49) Thus, future interventions may benefit from considering point-of-care reminders that simultaneously prompt physicians and patients to discuss HPV vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Guideline implementation likely will require a multifaceted approach 24 and computer reminders represent a promising component for successful implementation. 25 Electronic health record prompts already show potential for improving HPV vaccine uptake; 26 incorporating reminders about practice guidelines may also facilitate improved HPV vaccine recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two relatively intensive multi-component provider-focused interventions also resulted in significant, though somewhat modest increases in HPV vaccination rates (18,19). Using a retrospective cohort design, Ruffin and colleagues found that practices that had an EHR reminder prompt system had higher HPV vaccine rates than practices without an EHR prompt (20). In contrast, a recently published randomized study of EHR prompts found that they had no effect on HPV vaccination rates (21).…”
mentioning
confidence: 89%